ENHANCING ARTISTIC SKILLS IN GRADES 5–7 THROUGH SEQUENTIAL LESSON PLANNING - Boboqulov Javohir Hamzayevich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article examines the role of sequential lesson planning in improving the artistic skills of students in grades 5–7. The study emphasizes how a structured, stage-by-stage approach to art instruction supports the development of creativity, visual literacy, and critical thinking. By organizing lessons in a logical progression—from foundational techniques to more complex creative applications—teachers can ensure consistent skill growth and maintain students’ engagement throughout the learning process. The research highlights the effectiveness of modern pedagogical strategies such as project-based learning, flipped classrooms, and digital visualization tools in enhancing fine art education. The proposed model demonstrates that systematically planned lessons contribute to both the cognitive and emotional development of students, preparing them to interpret and express the visual world artistically and meaningfully.